An Analysis of Figurative Language in James Arthur’s Song Lyrics - Wirayuda, Andikha Prabu; Abdussamad, Zainuddin; Syarifaturrahman, Wahyu Kamil; Supatmiwati, Diah (Humanitatis : Journal of Language and Literature, 2025)
This study aims to identify the types of figurative language used in James Arthur’s songs and also to analyze the meanings conveyed through these figurative language elements. The method of this study is descriptive qualitative, focusing on the analysis of figurative language entitled “The Analysis of Figurative Language in James Arthur’s Songs.” This study employed an observational technique for data collection and content analysis as a supporting method. The study utilized Geoffrey Leech’s (1981) theory to analyze the figurative language present in the selected songs. The results of this study found 31 data points, which consist of 15 (fifteen) hyperboles, 4 (four) metaphors, 6 (six) similes, 2 (two) metonymies, 2 (two) personifications, 1 (one) litotes, and 1 (one) irony. This study underscores the significance of figurative language in music, suggesting that analyzing lyrics can provide listeners with a deeper understanding of emotional expressions and themes.